A novel multifunctional anti-CEA-IL15 molecule displays potent antitumor activities - Liu Y; Wang Y; Xing J; Li Y; Liu J; Wang Z (Dove Medical Press, 2018)
Yue Liu,1,2 Yanlan Wang,1,2 Jieyu Xing,1,2 Yumei Li,1,2 Jiayu Liu,1,2 Zhong Wang1,2 1School of Pharmaceutical Sciences, 2Center for Cellular and Structural Biology, Sun Yat-Sen University, Guangzhou, People’s Republic of China Introduction: Interleukin-15 (IL-15) is an immunomodulatory cytokine. It can activate and expand cytotoxic CD8 T lymphocytes and natural killer cells, leading to potent antitumor effects. Various forms of IL-15 are now in different stages of development for cancer immunotherapy. One of the major issues with IL-15 or IL15–IL15Rα fusion is high toxicity due to systemic activation of immune cells. Materials and methods: In this study, we engineered a nanobody–cytokine fusion molecule, anti-CEA-IL15, in which an anti-CEA nanobody was linked to an IL15Rα–IL15 fusion. The nanobody–cytokine fusion exhibited multiple mechanisms to kill tumor cells, including promoting immune cell proliferation and directing antibody-dependent cytotoxicity against CEA-positive tumor cells. Results: In xenograft models, anti-CEA-IL15 was localized in the tumor microenvironment and exhibited more potent antitumor activities than non-targeting IL-15, supporting potential application of this multifunctional fusion molecule in tumor immunotherapy. Conclusion: We generated and validated a tumortargeting fusion protein, anti-CEA-IL15, which has potent cytokine activity to activate and mobilize the immune system to fight cancer cells. Such strategies may also be applied to other cytokines and tumor-targeting molecules to increase antitumor efficacy. Keywords: immunotherapy, IL-15, nanobody, CEA, antibody–cytokine fusion